Healthcare-associated infections: an overview of global strategies and challenges in minimizing infection transmission : Healthcare-associated infections - Abalkhail, Adil; Marzouk, Eman (Cellular and Molecular Biology, 2025)
Healthcare-associated infections (HAIs) are a major cause of mortality, significantly impacting morbidity rates. They can occur during hospital care or 3 to 30 days after discharge. In developing countries, ten patients acquire at least one HAI for every 100 hospital admissions, compared to seven in high-income countries. The World Health Organization (WHO) defines HAIs as infections that may develop 2 to 3 days after admission or discharge, often undetected at hospital presentation. Many pathogens have developed antibiotic resistance, limiting effective treatments. This review summarizes international initiatives to combat HAIs, based on a literature review using Google Scholar and PubMed. Handwashing remains a key method for preventing HAIs, relying on strict adherence to hygiene protocols by nursing professionals. Maintaining a safe medical environment reduces the transmission of harmful bacteria, especially multi-drug-resistant pathogens. Hand hygiene and antibiotic stewardship are essential for preserving antibiotic effectiveness. Vaccine development can help mitigate HAIs by targeting multidrug-resistant organisms like Staphylococcus aureus and Clostridium difficile. A comprehensive understanding of prevention strategies and challenges is urgently needed.